Pengaruh Konfigurasi Ruang Kota Pada Pengembangan Sustainable Tourism Kecamatan Jabon, Sidoarjo - Mutia, Fairuz; Avenzoar, Azkia; Zahroh, Fatimatuz (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
Sidoarjo Spatial Planning's data indicates that Jabon area is planned to be a DEM tourist area and secondary mixed-used. Some tourism activities have started to exist but are only concentrated in the Tlocor area, while other areas in the area are still very minimal in facilities. Is it true then that the configuration of urban space in Jabon District can accommodate the city's development – which is now leading to tourism? This research is qualitative research with a phenomenological approach. The chosen space syntax analysis technique is used as a heuristic tool to discuss fundamental concepts. The study results indicate a relationship between the configuration of urban space and the concept of sustainable tourism development. Configuration can be seen in terms of accessibility and economic improvement that can be done by knowing the parts that can be mobility options and are connected to other urban spaces. Accessibility in the area can be developed by evaluating the existing road network so that connectivity can be better and human mobility to and from tourist areas is higher.